1998
DOI: 10.1007/s11745-998-0289-4
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine palmitoyltransferase I, carnitine palmitoyltransferase II, and Acyl‐CoA oxidase activities in atlantic salmon (Salmo salar)

Abstract: Salmon farmers are currently using high-energy feeds containing up to 35% fat; the fish's capability of fully utilizing these high-energy feeds has received little attention. Carnitine is an essential component in the process of mitochondrial fatty acid oxidation and, with the cooperation of two carnitine palmitoyltransferases (CPT-I and CPT-II) and a carnitine acylcarnitine transporter across the inner mitochondrial membrane, acts as a carrier for acyl groups into the mitochondrial matrix where beta-oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 55 publications
(43 reference statements)
3
47
0
Order By: Relevance
“…With the importance of lipid as an energy source in most fish species, particularly salmonids and marine fish, there have been several studies on fatty acid oxidation in fish (Crockett and Sidell 1993;Kiessling and Kiessling 1993;Frøyland et al 1998Frøyland et al , 2000Fjermestad et al 2000;Torstensen et al 2000;Nanton et al 2003;Vegusdal et al 2004;Oxley et al 2005;Stubhaug et al 2005aStubhaug et al ,b,c, 2006.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the importance of lipid as an energy source in most fish species, particularly salmonids and marine fish, there have been several studies on fatty acid oxidation in fish (Crockett and Sidell 1993;Kiessling and Kiessling 1993;Frøyland et al 1998Frøyland et al , 2000Fjermestad et al 2000;Torstensen et al 2000;Nanton et al 2003;Vegusdal et al 2004;Oxley et al 2005;Stubhaug et al 2005aStubhaug et al ,b,c, 2006.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to supplying essential fatty acids, dietary lipid is also a major energy source for fish, including salmon (Frøyland et al 1998. Indeed, in vivo stable isotope studies in rainbow trout have shown that the vast majority of dietary 18:3n-3 was oxidized rather than utilized for HUFA synthesis (Bell et al 2001b;Bell and Dick 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively high levels of fatty acid oxidation have been reported for red muscle and heart in trout, whereas liver, kidney and white muscle have only limited capacity to oxidize fatty acids (Henderson and Tocher, 1987). In recent studies, white muscle was shown to be a quantitatively important site of fatty acid catabolism in salmon, particularly juveniles (Frøyland et al, 1998 but liver was not a major site of mitochondrial or peroxisomal β-oxidation . However, in the present study, hepatocytes and enterocytes showed similar values for β-oxidation activities, although enterocyte fatty acid oxidation activities were generally slightly higher than in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…(Henderson and Sargent, 1985;Singer et al, 1990). Fatty acid oxidation is an important source of energy in several tissues in fish in addition to liver, including heart and red muscles and, recently, white muscle has been reported as playing a significant role in overall fatty acid oxidation in Atlantic salmon (Froyland et al, 1998(Froyland et al, ,2000. At a cellular level, peroxisomes are another site of β-oxidation in mammals where they are possibly specifically utilised in the initial chain shortening prior to conventional β-oxidation of very long chain, highly unsaturated or unusual fatty acids.…”
Section: Fatty Acid Catabolismmentioning
confidence: 99%